Pengaruh Social Media Marketing, Harga dan Kualitas Produk Terhadap Keputusan Pembelian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The purchasing decision is a stage in the decision-making process that leads consumers to make a choice. Several factors influence the purchasing decision, such as social media marketing, price, and product quality. Social media marketing is the process of creating beneficial relationships through social media platforms. Price refers to the amount of money charged for a product or service. Meanwhile, product quality is the characteristic of a product that has the ability to meet customer needs. The purpose of this study is to determine the influence of social media marketing, price, and product quality on purchasing decisions both partially and simultaneously. The research was conducted on The Originote skincare products. The population for this study consists of consumers using The Originote skincare, which is considered infinite in number. The sample size was determined using the Hair theory, resulting in 95 participants. Data was collected through interviews, documentation, and questionnaires, measured using a Likert scale. The analysis technique used was multiple linear regression. The results show that the independent variables (X) have a positive and significant effect on the dependent variable (Y) both partially and simultaneously. Recommendations include increasing interaction with consumers, adjusting the selling price to match the quality and benefits of the product, and paying attention to product packaging to improve consumer purchasing decisions.